HUBUNGAN STATUS GIZI DAN PEMENUHAN ZAT GIZI DENGAN TINGKAT PRODUKTIVITAS PADA PEKERJA DI PT PELITA ADI PRATAMA DESA SEI MERBAU TANJUNG BALAI - Anggi Isnani Parinduri (Jurnal Penelitian Kesmasy, 2021)
One of the factirs that influence work productivity is the level of nutritional intake of workers as seen from the nutritional status of worker. A person with good nutrition will have better work capacity and endurance, and vice versa in worker with poor nutritional conditions and with a heavy workload will disrupt work and reduce the level of work productivity. This study aims to determine the relationship of nutritional status and nutrient fulfillment with the level of productivity in workers in Pelita Adi Pratama village, Sei Merbau Tanjung Balai in 2020. This research is a quantitative study with cross sectional design. The population in this study were all workers at PT Pelita Adi Pratama in Sei Merbau Tanjung Balai village. Samples of 34 were conducted in total sampling and data collection methods were taken by questionnaire. Bivariate data analysis used Chi Square test with a confidence level of 95%, α = 0,05. Based on the bivariate results there is a relationship between nutritional status and the level of productivity in workers (p value = 0,010), there is no relationship between the fulfillment of productivity ( p value = 0,481), there is no relationship between the fulfillment of carbohydrate nutrients and the level of productivity (p value = 0,535), there is no relationship between the fulfillment of protein nutrients with the level of productivity (p value = 0,579), there is no relationship between the fulfillment of fat nutrients with the level of productivity (p value = 0,624). It is recommended for workers to better understand and know the nutritional needs needed by each so that they can apply it in everyday life.